A study of drug utilization pattern in patients with hypertension in a tertiary care hospital - Ray, Namit; Syiem, Reuben P.; Wahlang, Julie B.; Raj, Krishnamoorthi (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Hypertension, a leading global health concern, poses significant risks to vital organs such as the heart, brain, and kidneys. Effective management remains a challenge, especially in countries like India, where cardiovascular diseases are a major contributor to mortality. This study aimed to evaluate the drug utilization patterns of antihypertensive drugs and associated prescribing practices in a tertiary care teaching hospital. Methods: A hospital-based cross-sectional descriptive study was conducted from January to October 2023 in the Departments of Medicine and Cardiology. The study included patients diagnosed with hypertension aged 18 years or older. Data on prescribed antihypertensive drugs, including drug type, dosage and comorbidities, were collected and analyzed. Results: A total of 230 prescriptions were analyzed, with 75.59% of patients receiving monotherapy. Amlodipine was the most commonly prescribed drug, used in 87.5% of monotherapy cases. Combination therapies were prescribed to 24.41% of patients, with the most common combinations being Amlodipine + Atenolol and Losartan + Hydrochlorothiazide + Amlodipine. Diabetes mellitus was the most frequent comorbidity observed, affecting 60 patients. A significant portion of prescriptions (59%) was written using brand names, and 41% were written using generic names. Conclusion: Future research should focus on enhancing patient adherence, optimizing treatment regimens, and continuously monitoring prescribing patterns to improve hypertension management and reduce associated health burdens.